Value creation and value capture in Indian garment sector bargaining - Russell Morton (Yale University, Economic Growth Center, 2025)
This paper examines creation and distribution of surplus from global value chains (GVCs) in low- and middle-income country (LMIC) domestic supply chains. While GVC participation can enhance growth and productivity, low prices paid to small input suppliers raise concerns that gains from GVC participation accrue to the large exporters (the buyers). Supply-chain transactions often occur in bargained agreements with non-price terms that increase small supplier surplus, such as quantity stability and other insurance-like terms. Therefore, low input prices reflect both buyers' share of surplus generated by non-price terms and buyer capture. I enrich a Nash bargaining model to study how both i) value creation through insurance-like agreement terms that mitigate spot market frictions and ii) value capture from buyers threatening to replace external suppliers with in-house production affect prices paid to small, risk-averse suppliers. Using novel transaction data from an Indian garment manufacturer and its nearly 500 fabric suppliers, I estimate a structural model to decompose discounts into value creation and capture. Results illustrate that discounts reflect value creation rather than buyer capture; difference-in-differences estimates yield consistent findings. Counterfactual analyses highlight that increasing buyer competition has limited effects on prices paid to small risk-averse suppliers, whereas introducing profit insurance substantially increases prices they receive.
Keywords: D22; F63; L14; O12; 330; Globale Wertschöpfungskette; Lieferkette; Betriebliche Wertschöpfung; Bekleidungsindustrie; Textilindustrie; Indien